Farm size and profitability: The village as collateral factor - Cristian C. Merce; Emilian Merce; Cristina Bianca Pocol (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
The goal of the study is to analyse and compare agrarian structures in several EU countries, analysed separately according to their degree of economic consolidation. The study points out that, in order to characterize the agrarian structures of a country, is not sufficient to determine the average size of farms. Such averages are the result of different distributions of farmland according to size categories, which are valuable sources of analysis in terms of the impact of agricultural structures on the modernization of production processes as well as for achieving substantial economic performance. An important objective of the paper is to evaluate the numerical influence of farm size on the economic results, using regression and correlation methods. The study reveals that size is a necessary condition for the achievement of economic performance, but it is not sufficient. A causalities comparison between countries with a consolidated economic situation and the ones economically precarious confirm this fact, concluding also that, in addition to size, farms must provide a substantial capitalization as well as modern technical equipment. The paper underlines also the fact that the precarious capitalization of farms, along with feudal agrarian structures, causes paradoxal situations, the economic effect being found in an inverse relationship to size.
Keywords: 330; farm size; economic effects; causality; paradoxal situations